Environmental Protection and Optimal Taxation - Eskeland, Gunnar S. (World Bank, Washington, DC, 2014)
Struck by the fact that economists did not have a plausible model for why emissions standards, and mandated technologies, play a dominant role in pollution control, the author sought answers to two questions: 1) Should one stimulate emissions reductions by firms, and households, rich and poor, in the same way? 2) How should one combine instruments that make activities cleaner, with instruments that shift the economy toward less-polluting activities? Using clean air as an example of a pure public good, he shows the role of emissions taxes, or such surrogate instruments, as emissions standards, and presumptive Pigouvian taxes. To illustrate the combination of demand management, and technical controls, he computes a marginal cost curve for emissions reductions in the form of cleaner cars, and fuels. And he estimates a demand model for cars, and driving. The result: under the assumption that revenue, and re-distributive transfers bear no premia, the cost of reducing pollution in Mexico City increases forty four percent if an emissions standards program is used, and the presumptive Pigouvian tax on gasoline is not. The important finding, as costly redistribution, and revenue generation are introduced, is that this influences the general scheme of taxation (in well-known ways), and it influences the conditions for optimal environmental quality in accordance with Pigou's conjecture. However, it does not change, or invalidate the rankings of technologies, and interventions on the control cost curve, nor does it change the role of demand management in environmental protection.